Investment planning and the input-output model in postwar Europe - Vincent Carret (Duke University, Center for the History of Political Economy (CHOPE), 2022)
As economic planners sought to rebuild Europe in the unstable postwar period, economic expertise was called upon to help in the drawing of national budgets and to inform economic and planning policies. A tool that circulated from academia to economic administrations was the input-output framework that had been developed by Wassily Leontief since the 1930s. As Leontief came into contact with other economists and with the goals of economic administrations, his framework was repurposed to give answers to the questions of economic planners. Statisticians and economists in Western Europe worked to integrate the input-output framework with the developing national accounts. Looking at their work with a particular focus on investment and development policies, I bring new insights on the role of experts, by showing that the input-output model had little impact on the actual coordination of economic policies.
Keywords: B23; O21; C67; L52; P11; B31; 330; Leontief; input-output; planning; investment; Europe; instability